The Effectiveness of Asystasia gangetica (L.) T. Anderson Leaf Extract as a Corrosion Inhibitor for Mild Steel in Hydrochloric Acid Medium - Karina Ventika Sari; Emriadi; Yeni Stiadi (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2025)
The inhibition effectiveness of the extract in hydrochloric acid solution was analyzed using the weight loss method at 30 °C for 7 hours to determine the corrosion rate and inhibition efficiency. The active compounds were identified through phytochemical tests, while the adsorption type was determined based on thermodynamic parameters. Characterization of surface changes on mild steel was carried out using UV-Vis spectroscopy and Field Emission Scanning Electron Microscopy (FESEM). The results revealed the presence of flavonoids, alkaloids, steroids, triterpenoids, and phenolics, which contribute to the adsorption process on the mild steel surface. The lowest corrosion rate was obtained at a concentration of 8 g/L, namely 0.43 mg/cm².h, with the highest inhibition efficiency of 73.42%. The R² value approaching 1 follows the Langmuir adsorption isotherm, with a  value of -23.79, indicating that EDAG molecules are adsorbed on the mild steel surface through mixed adsorption. Surface morphology analysis showed a smoother steel surface after immersion in the inhibitor solution, indicating the formation of a protective layer. Thus, compared to previous studies, EDAG exhibits higher inhibition efficiency and demonstrates potential as an environmentally friendly corrosion inhibitor alternative.